2012
DOI: 10.1186/1749-8090-7-3
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia-modified albumin use as a prognostic factor in coronary bypass surgery

Abstract: BackgroundVarious types of markers have been used so far in order to reveal myocardial perfusion defect. However, these markers usually appear in the necrosis phase or in the late stage. Having been the focus of various investigations recently, ischemia-modified albumin (IMA) is helpful in establishing diagnosis in the early stages of ischemia, before necrosis develops.Methods and Results30 patients that underwent only coronary bypass surgery due to ischemic heart disease within a specific period of time have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 31 publications
3
22
0
Order By: Relevance
“…Serum albumin is a major antioxidant for the respiratory tract 19 because the N-terminal region of albumin eliminates free oxygen radicals and binds transition metals such as cobalt, copper, and nickel. 20 The elevation of IMA is directly associated with free radicals generated during ischemia. 20 IMA levels are elevated in cardiac ischemia, cerebrovascular occlusion, pulmonary ischemia, gastrointestinal ischemia, and muscle ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum albumin is a major antioxidant for the respiratory tract 19 because the N-terminal region of albumin eliminates free oxygen radicals and binds transition metals such as cobalt, copper, and nickel. 20 The elevation of IMA is directly associated with free radicals generated during ischemia. 20 IMA levels are elevated in cardiac ischemia, cerebrovascular occlusion, pulmonary ischemia, gastrointestinal ischemia, and muscle ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…20 The elevation of IMA is directly associated with free radicals generated during ischemia. 20 IMA levels are elevated in cardiac ischemia, cerebrovascular occlusion, pulmonary ischemia, gastrointestinal ischemia, and muscle ischemia. 8,19,20 Hypoxia was demonstrated to impair endotheliumdependent pulmonary artery relaxation in patients with severe COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated IMA levels have been shown in such ischemic events and hypoxemia (13,27,28). Previous studies have shown that IMA reflects the magnitude and duration of ischemia induced during percutaneous coronary intervention and exercise test for coronary syndrome, and that it is a sensitive marker for the identification of acute cardiac ischemia (29)(30)(31)(32). The most important characteristic that differentiates IMA from other cardiac ischemia markers is that it increases in the early phase.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] and is a good prognostic marker in chronic ischemic heart failure 16 and Coronary artery bypass graft surgery (CABG). 17 This is positive in a variety of conditions giving rise to tissue ischemia. 18,19 Our study highlights the importance of evaluating patient populations for testing as more false positive elevations in ischemia modified al-(STEMI) was diagnosed if there was ST segment elevation >0.1mv in 2 or more contiguous leads with cardiac troponin (cTnT) >0.05ng/ml; non-ST-segment elevation myocardial infarction (NSTEMI) was diagnosed if EKG did not show ST-segment elevation and troponin (cTnT) was >0.05ng/ml.…”
Section: Methodsmentioning
confidence: 99%